2007
DOI: 10.1091/mbc.e07-01-0035
|View full text |Cite
|
Sign up to set email alerts
|

Gleevec Increases Levels of the Amyloid Precursor Protein Intracellular Domain and of the Amyloid-β–degrading Enzyme Neprilysin

Abstract: Amyloid-␤ (A␤) deposition is a major pathological hallmark of Alzheimer's disease. Gleevec, a known tyrosine kinase inhibitor, has been shown to lower A␤ secretion, and it is considered a potential basis for novel therapies for Alzheimer's disease. Here, we show that Gleevec decreases A␤ levels without the inhibition of Notch cleavage by a mechanism distinct from ␥-secretase inhibition. Gleevec does not influence ␥-secretase activity in vitro; however, treatment of cell lines leads to a dose-dependent increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 69 publications
2
39
0
Order By: Relevance
“…However, our findings do give rise to the possibility that imatinib can decrease A␤ levels by some alternative mechanism independent of GSAP. For instance, it has been shown that imatinib can regulate A␤ and AICD levels in cells by a mechanism involving increased neprilysin expression (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…However, our findings do give rise to the possibility that imatinib can decrease A␤ levels by some alternative mechanism independent of GSAP. For instance, it has been shown that imatinib can regulate A␤ and AICD levels in cells by a mechanism involving increased neprilysin expression (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…Although the differences between the original study of Pardossi-Piquard et al [74] and those of Chen and Selkoe [79] have been discussed [80], these studies need to be verified independently. Indirect support for the regulation of the NEP gene by AICD was recently published by Eisele et al [81]. They showed that Gleevac caused an increase in AICD levels by an unknown mechanism, possibly by decreasing the rate of AICD catabolism.…”
Section: Regulation Of the Neprilysin Genementioning
confidence: 93%
“…To detect total A␤, equal amounts of conditioned cell media were analyzed on 12% NuPAGE gels using MES running buffer (Invitrogen). For analysis of APP C-terminal fragments, separation of A␤40/A␤42 and Western blot detection of proteins was carried out as described previously (29). Representative blots from at least three independent experiments are shown.…”
Section: Generation Of Transgenic Mice Expressing Wild Type Human Brimentioning
confidence: 99%